Presence of a functional nitrate assimilation pathway in mycobacterium smegmatis - Khan, Arshad; Akhtar, Shamim; Ahmad, Jawid N.; Sarkar, Dhiman (Microbial Pathogenesis, 2008)
Ability of Mycobacterium smegmatis to assimilate nitrate was evaluated in its active and dormant phase. Nitrate (10 mM), nitrite (0.5 mM) and ammonia (10 mM)allowed growth of M. smegmatis concomitant with their complete depletion from the culture in 144, 120 and 96 h, respectively, when used as sole nitrogen Source. Azide (50 mu M) stopped the growth of M. smegmatis when nitrate was used as sole nitrogen source. L-methionine-S-sulfoximine (L-MSO), which is a well-known inhibitor of glutamine synthetase, an enzyme also involved in nitrogen metabolic pathway, when applied at 10 mu g/ml concentration, completely inhibited the growth of the organism when nitrate or nitrite was used as sole nitrogen source. There was no effect of either azide or L-MSO at above concentrations on the growth of the organism when asparagine or ammonia was used as sole nitrogen source. More significantly, utilization of nitrate, nitrite and ammonia continued even in oxygen depletion induced dormant culture at the rates of 289, 25 and 354 mu M/day, respectively. These rates were 5-8 times slower than the rates of 1966, 127 and 2890 mu M/day, respectively, in active replicating phase. In the presence of azide (50 mu M) and L-MSO (10 mu g/ml), 2.1 and 1.51 logs reduction in viability of dormant M. smegmatis was observed using nitrate and nitrite, respectively, as sole nitrogen source. Altogether, the results indicated the presence of nitrate assimilation pathway operating in both active and dormant stage of M. smegmatis. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: Dormant bacilli; Glutamine synthetase; L-methionine-S-sulfoximine; Mycobacterium smegmatis; Nitrate assimilation